Where is my mind? Mark Rowlands on the vehicles of cognition - Andreas Elpidorou (Avant, 2012)
Do our minds extend beyond our brains? In a series of publications, Mark Rowlands has argued that the correct answer to this question is an affirmative one. According to Rowlands, certain types of operations on bodily and worldly structures should be considered to be proper and literal parts of our cognitive and mental processes. In this article, I present and critically evaluate Rowlands' position.